Evaluation of late cardiac effects after multisystem inflammatory syndrome in children - De Wolf, Rik; Zaqout, Mahmoud; Tanaka, Kaoru; Muiño-Mosquera, Laura; van Berlaer, Gerlant; Vandekerckhove, Kristof; Dewals, Wendy; De Wolf, Daniël (Frontiers in Pediatrics, 2023)
Introduction: Multisystem Inflammatory Syndrome in Children (MIS-C) is associated with important cardiovascular morbidity during the acute phase. Follow-up shows a swift recovery of cardiac abnormalities in most patients. However, a small portion of patients has persistent cardiac sequelae at mid-term. The goal of our study was to assess late cardiac outcomes ofMethods: A prospective observational multicenter study was performed in children admitted with MIS-C and cardiac involvement between April 2020 and March 2022. Follow-up by NT-proBNP measurement, echocardiography, 24-Hour Holter monitoring and cardiac MRI (CMR) was performed at least 6 months after MIS-C diagnosis.We included 36 children with a median age of 10 (8.0-11.0) years and 21 (58%) were female. At diagnosis, all patients had an elevated NT-proBNP, 39% had a decreased LVEF (< 55%). ECG abnormalities were present in 13 (36%) patients, but none presented with arrhythmia. Almost two thirds of patients (58%) had echocardiographic abnormalities such as coronary artery dilation (20%), pericardial effusion (17%) and mitral valve insufficiency (14%). Decreased echocardiographic systolic LV function was detected in 14 (39%) patients.Follow-up visit was done at a mean time of 12.1 (± 5.8) months (range 6-28 months). ECG normalized in all except one and no arrythmias were detected on 24-hour Holter monitoring.None had persistent coronary artery dilation or pericardial effusion. NT-pro-BNP level and echocardiographic systolic LV function normalized in all patients except for one who had a severely reduced EF. LV global longitudinal strain (GLS), as marker of subclinical myocardial dysfunction, was decreased (z < -2) in 35%. CMR identified one patient with severely reduced EF and extensive myocardial fibrosis requiring heart transplantation. None of the other patients had signs of myocardial scarring on CMR.Late cardiac outcomes after MIS-C, if treated according to current guidelines, are excellent. CMR does not show any myocardial scarring in children with normal systolic LV function. However, a subgroup has a decreased GLS at follow-up, possibly as a reflection of persistent subclinical myocardial dysfunction.